2019
DOI: 10.1105/tpc.18.00577
|View full text |Cite
|
Sign up to set email alerts
|

Variation in Expression of the HECT E3 Ligase UPL3 Modulates LEC2 Levels, Seed Size, and Crop Yields in Brassica napus

Abstract: Identifying genetic variation that increases crop yields is a primary objective in plant breeding. We used association analyses of oilseed rape/canola (Brassica napus) accessions to identify genetic variation that influences seed size, lipid content, and final crop yield. Variation in the promoter region of the HECT E3 ligase gene BnaUPL3.C03 made a major contribution to variation in seed weight per pod, with accessions exhibiting high seed weight per pod having lower levels of BnaUPL3.C03 expression. We defin… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
40
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 42 publications
(41 citation statements)
references
References 54 publications
(72 reference statements)
1
40
0
Order By: Relevance
“…The authors suggest that the higher levels of LEC2 protein could contribute to an extended period of seed maturation during which lipids can accumulate. Miller et al (2019) noted that the genetic variation in B. napus BnaUPL3.C03 promoters has yet to be selected for in the breeding of B. napus or other oilseed crops, suggesting a new approach to increasing oil content (54).…”
Section: The E3 Ligase Upl3 Affects Seed Size and Lipid Contentmentioning
confidence: 99%
“…The authors suggest that the higher levels of LEC2 protein could contribute to an extended period of seed maturation during which lipids can accumulate. Miller et al (2019) noted that the genetic variation in B. napus BnaUPL3.C03 promoters has yet to be selected for in the breeding of B. napus or other oilseed crops, suggesting a new approach to increasing oil content (54).…”
Section: The E3 Ligase Upl3 Affects Seed Size and Lipid Contentmentioning
confidence: 99%
“…So far, it has been reported that plant UPLs, especially UPL3 and UPL5, are involved in trichrome development, leaf senescence, vascular development, seed size, crop yields, and immunity response [8,35,36,37,38,39]. The upl5 mutant shows a premature aging phenotype, where the mechanism has been revealed by Ying Miao and Ulrike Zentgraf that UPL5 protein is able to target the transcription factor (TF) WRKY53, which is a key senescence transcription factor, for its ubiquitination and degradation [35].…”
Section: The Roles Of Hect E3s In Cell Senescence/agingmentioning
confidence: 99%
“…That is, high SWPP lines had low BnaUPL3.C03 expression and vice versa. Miller et al (2019) found that Arabidopsis loss-of-function upl3 mutants (upl3-4 and upl3-5) had seeds ;10% larger than the wild type and had a 12% increase in seed lipid content. In comparison, overexpression of AtUPL3 using the 35S promoter (35S:3HA-UPL3 transgenic) reduced seed size and lipid content.…”
mentioning
confidence: 99%
“…Identifying natural genetic variation, understanding how it influences traits, and utilizing it for crop improvement is a major objective in plant science. Miller et al (2019) have identified genetic variation in the promoter region of BnaUPL3.C03 from a panel of Brassica napus accessions that can influence seed size, lipid content, and final crop yield. They establish a mechanism in which reduced expression of BnaUPL3.C03, encoding a HECT E3 ubiquitin ligase, leads to elevated levels of LEAFY COTYLEDON 2 (LEC2), a transcription factor controlling seed maturation.…”
mentioning
confidence: 99%
See 1 more Smart Citation